The microstructure and thermodynamic behavior of as-cast U-24Pu-15Zr: Unexpected results and recommendations for U-Pu-Zr fuel research methodology - Hirschhorn, Jacob; Aitkaliyeva, Assel; Adkins, Cynthia; Tonks, Michael (Journal of nuclear materials, 2019)
Minor actinide transmutation fuels, of which U-Pu-Zr is one of the most promising, have been the subject of renewed interest for fast reactor applications. Unfortunately, we lack the understanding necessary to make quantitative, mechanistic predictions about the complex phase behaviors exhibited by U-Pu-Zr. This prevents the efficient development and implementation of U-Pu-Zr fuels. Herein, we use state of the art experimental and mesoscale simulation techniques to examine and predict the behavior of U-24Pu-15Zr (weight percent). Experimental and simulated microstructural and phase stability results are compared to one another and to accepted reference data. Experiments revealed a heterogeneous microstructure composed of αZr, ZrO2, δ, βPu, and ζ at room temperature. The unexpectedly high ratio of βPu to ζ is believed to arise from non-equilibrium and surface effects, as both passivation and Pu and Zr segregation were observed in the samples. A modeling technique based on the overall bulk free energy is devised to estimate the extent of a microstructure's departure from equilibrium. Agreement between the datasets is used to justify a set of recommendations for the further study of U-Pu-Zr fuels. These address deficiencies in our fundamental knowledge, fuel fabrication and handling techniques, characterization methods and procedures, modeling capability, and use of coupled experiments and mesoscale simulations. •As-cast U-24Pu-15Zr samples exhibit passivation and surface segregation behaviors.•Surface and near-surface characterizations are obscured by surface effects.•Reference, experimental, and simulated transition temperatures are inconsistent.•Coupled experiments and mesoscale simulations will enhance metallic fuel research.